Big Data, Knowledge Mapping for Sustainable Development: A Water Quality Index Case Study - Lei Zhang (Emerging Science Journal, 2019)
Water quality assessment is an increasingly important area of environmental study. Assessment of water quality can be a process that includes multiple factors, which can have an influence on water quality. Researchers have developed many evaluation indices in order to display the results of water quality evaluations more intuitively. The water quality index has been an important field in sustainable water quality management. This research, based on the papers published of 20 years from the Web of Science, analyzed the data by using CiteSpace 5.0. The result shows the direction, frontiers, and hotspots of the water quality index. Research from institutes, research keywords, word frequency, quoted literature, and subjects The result shows that, in view of the world, India, China, the US, Brazil, and Iran are major countries. From the hotspots and frontiers of research, key words like "water quality management" and "drinking water quality" are the main research hotspots and frontiers of social network in the contamination of water and water quality problems in China and India. This study provides a method for scientists to keep up with the situation of the study on water quality management and puts forward suggestions for further research on sustainable water quality index.